2019
DOI: 10.3390/ma12050748
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Molybdenum–Vanadium Mixed Oxides in Selective Oxidation and Disproportionation of Toluene

Abstract: This study deals with the behavior of molybdenum–vanadium (Mo/V) mixed oxides catalysts in both disproportionation and selective oxidation of toluene. Samples containing different Mo/V ratios were prepared by a modified method using tetradecyltrimethylammonium bromide and acetic acid. The catalysts were characterized using several techniques: nitrogen adsorption–desorption isotherms, X-Ray diffraction (XRD), ammonia temperature-programmed desorption (TPD-NH3), temperature-programmed reduction by hydrogen (H2-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The molybdenum oxide appeared to be a mixture of MoO 2 and MoO 3 . As observed in the XRD spectrum, besides the peaks of FTO, there are some other peaks which may belong to MoO 2 as the reduction-decomposition product of the heptamolybdate salt [68] and MoO 3 as the calcination products at 350 °C [69,70]. More specifically, the peaks at 2θ = 9:0, Next, the surface morphology and composition of MoO x /MoS 2 thin film deposited at 25 V in 10 minutes were analyzed by field emission scanning electron microscope with Oxford Energy-dispersive X-ray Spectrometer (FE-SEM/EDS).…”
Section: Characterization Of Moomentioning
confidence: 95%
“…The molybdenum oxide appeared to be a mixture of MoO 2 and MoO 3 . As observed in the XRD spectrum, besides the peaks of FTO, there are some other peaks which may belong to MoO 2 as the reduction-decomposition product of the heptamolybdate salt [68] and MoO 3 as the calcination products at 350 °C [69,70]. More specifically, the peaks at 2θ = 9:0, Next, the surface morphology and composition of MoO x /MoS 2 thin film deposited at 25 V in 10 minutes were analyzed by field emission scanning electron microscope with Oxford Energy-dispersive X-ray Spectrometer (FE-SEM/EDS).…”
Section: Characterization Of Moomentioning
confidence: 95%
“…One of the strategies taken to improve the performance of vanadium oxides is a mixture with other semiconductors including bismuth vanadate (BiVO4) [ 49,50 ] and molybdenum trioxide (MoO3). [ 51–53 ] Arunachalam et al showed that the incident photon to current efficiency improved more than 50% at the wavelength of 425 nm by forming a heterostructure of normalV2normalO5/BiVO4, [ 49 ] and Chuai et al showed that normalV2normalO5/MoO3 composite exhibited enhanced visible‐light photocatalytic activity because of the formation of heterostructures at the interface between normalV2normalO5 and MoO3. [ 51 ]…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent interaction , and morphology regulation , are practiced as effective manipulations to elevate the surface active site density and, in turn, the activation capability. Molybdenum has been widely selected as the active component in the oxidation reaction, and the higher performance at lower temperature is expected as promising with higher selectivity of the product. In a recent study of catalyst screening for EL to EP, Huchede et al reported that among selected V- or Mo-containing catalysts, MoO 3 exhibited the best yield of EP, which was 63% at 300 °C with 78% EL conversion.…”
Section: Introductionmentioning
confidence: 99%
“…As is generally accepted, the constitution and distribution of active components are crucial to the catalytic performance of oxide-based catalysts. 31,32,36 Notably, the MoV 2 O 8 phase has been reported as a remarkably active phase (approximately 3.5 times than the separate V 2 O 5 or MoO 3 ) in glycerol ODH reaction resulting from the valance state cycling of contained V active species and related dynamic formation of oxygen vacancies. 35 Temperature-Programmed Analysis.…”
Section: ■ Introductionmentioning
confidence: 99%